The Cost-Effectiveness of Rotavirus Vaccination in Malawi - Berry, Stephen A. (The University of Chicago Press, 2010)
Background. Rotarix (GlaxoSmithKline), a newly licensed rotavirus vaccine requiring 2 doses, may have the potential to save hundreds of thousands of lives in Africa. Nations such as Malawi, where Rotarix is currently under phase III investigation, may nevertheless face difficult economic choices in considering vaccine adoption. Methods. The cost-effectiveness of implementing a Rotarix vaccine program in Malawi was estimated using published estimates of rotavirus burden, vaccine efficacy, and health care utilization and costs. Results. With 49.5% vaccine efficacy, a Rotarix program could avert 2582 deaths annually. With GAVI Alliance cofinancing, adoption of Rotarix would be associated with a cost of $5.07 per disability-adjusted life-year averted. With market pricing, Rotarix would be associated with a base case cost of $74.73 per disability-adjusted life-year averted. Key variables influencing results were vaccine efficacy, under-2 rotavirus mortality, and program cost of administering each dose. Conclusions. Adopting Rotarix would likely be highly cost-effective for Malawi, particularly with GAVI support. This finding holds true across uncertainty ranges for key variables, including efficacy, for which data are becoming available.